(3GdeQJjI GdYdjG aj JaSjQ GdQDjGs - (3CHh YHO Gddg eMeO Hf YHO Gddg Hf QGTO GdHcQj GdbaUjs ((3ecI GdeTQaI s)
(3ChdgG (B:s
(3GdMeO ddg Pi GdYRI hGdLdGd hHYO aEfi cfJ ai HGchQI GdYeQ QMdJ Edi GdOjGQ GdeUQjI ddYde WGdHkG heeG YfjJ Hg Yde JYHjQ GdQDjG (B,(3ahVJ gPG GdeNJUQ , hVefJg LejY eG hUd Ydeg Edi hbO SejJg HGdeQJHI GdYdjG ai JaSjQ GdQDjG s
(3BNQgG (B:s
(3hbGd eQjV HGdMQGQI (B: (3QCjJ Cfi YHQJ GdLfI bGd (B: (3JYGai cedJ GdeQJHI GdYdjG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa eLehYI Bd jMi (B((3JUha (B84) s
Keywords: (3JYHjQ GdQDjGs